The quality of reporting randomized controlled trials in the dermatology literature in an era where the CONSORT statement is a standard. (1st June 2019) - Kim, D.Y.; Park, H.S.; Cho, S.; Yoon, H.S.
Summary: Background: The quality of reporting randomized controlled trials (RCTs) in the dermatology literature has not received much consideration since the late 2000s. Objectives: We aimed to assess the quality of recently reported RCTs published in dermatology journals, focusing on randomization processes, blinding and trial registration. Methods: We reviewed 2042 original articles and identified 141 primary reports of RCTs in four dermatology journals ( Journal of the American Academy of Dermatology, JAMA Dermatology, Journal of Investigative Dermatology and British Journal of Dermatology ) from January 2015 to December 2017. Details were extracted from articles, supplements and public trial registries. A multivariable logistic regression analysis was conducted to identify factors associated with optimal reporting quality. Results: Among the 141 RCTs, 99 (70·2%), 82 (58·2%) and 69 (48·9%) described methods used for randomization, allocation concealment and implementation, respectively. Most trials (126, 89·4%) reported blinding status; however, one‐third did not state the similarity of the intervention. Furthermore, 52 RCTs (36·9%) were not registered prospectively. Trials published in the British Journal of Dermatology and using central randomization were significantly associated with optimal reporting quality after adjusting for covariates. Conclusions: Several critical items in reporting RCTs, including allocation concealment, similarity of interventions in blinded trials and prospective trial registration, have remained unsatisfactory in the recent dermatology literature.